2017
DOI: 10.1002/acr.23212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clusters of Foot Pain Location in a Community Sample

Abstract: Five clusters of foot pain according to pain location were identified, all with distinct age, sex, and comorbidity profiles. These findings may assist in the identification of individuals at risk for developing foot pain and in the development of targeted preventive strategies and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
8
2
Order By: Relevance
“…We found a significant association between female sex and bilateral widespread foot and ankle pain class, but no association was seen between age and any of the classes. This is contrary to the results found by the North West Adelaide Health Study (Gill et al, 2017) which found forefoot, toe and nail pain occurring in older men, rearfoot and heel pain affected a high proportion of young individuals, and ball and arch pain was seen in younger females. The differences may be explained by the older population in our study where more individuals might have osteoarthritis and other chronic conditions than the North West Adelaide Health Study (Gill et al, 2017), where study participants ranged between 20 to over 75 years of age and were more likely to be affected by a broader range of foot conditions.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…We found a significant association between female sex and bilateral widespread foot and ankle pain class, but no association was seen between age and any of the classes. This is contrary to the results found by the North West Adelaide Health Study (Gill et al, 2017) which found forefoot, toe and nail pain occurring in older men, rearfoot and heel pain affected a high proportion of young individuals, and ball and arch pain was seen in younger females. The differences may be explained by the older population in our study where more individuals might have osteoarthritis and other chronic conditions than the North West Adelaide Health Study (Gill et al, 2017), where study participants ranged between 20 to over 75 years of age and were more likely to be affected by a broader range of foot conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…These differences could be explained by their population being younger than ours (≥18 years compared to ≥50 years), and their use of the Framingham foot manikin (Hannan et al, 2006) which required participants to have pain on ‘most days’, whilst our study used the Garrow foot manikin (Garrow et al, 2004) in which study participants were asked to shade the foot regions where they experienced pain in the past month. In the current study, the foot manikin was divided into 14 foot and ankle pain regions (seven regions on each foot), whereas the Adelaide study (Gill et al, 2017) divided foot pain into seven areas that were recorded across both feet. Therefore, our analysis provides the added advantage of being able to compare patient characteristics of unilateral foot pain symptoms to those with bilateral foot and ankle pain, in addition to evaluating patient characteristics of different foot pain regions (forefoot, midfoot and/or hindfoot).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations